Unveiling the potential of prostate-specific membrane antigen for precision diagnosis and therapy of prostate cancer: a radiopharmaceutical perspective - Hassan, Hishar; Othman, Muhamad Faiz; Ashhar, Zarif Naim; Abdul Razak, Hairil Rashmizal; Ahmad Saad, Fathinul Fikri (Penerbit Universiti Sains Malaysia, 2024)
Prostate-specific membrane antigen (PSMA) has proven to be an important target for diagnostic imaging in prostate cancer. As PSMA is overexpressed on the surface of prostate cancer cells, numerous targeted PSMA ligands have been developed. The emergence of PSMA targeting based on small molecules, such as the PSMA-11 ligand (or PSMA-HBED-CC), has led to breakthroughs, such as [68Ga]Ga-PSMA-11, for positron emission tomography (PET) imaging of biochemically recurrent or metastatic castration-resistant prostate cancer (mCRPC). In addition, the recent approval of [177Lu]Lu-PSMA-617 for the treatment of adult patients with PSMA-positive mCRPC represents an important milestone in prostate cancer therapy. These advances underscore the growing confidence in the use of PSMA-targeted radiopharmaceuticals for the diagnosis and treatment of prostate cancer patients. PSMA-targeted radiopharmaceuticals have been shown to significantly impact treatment planning and clinical decision-making and facilitate the customisation of treatment regimens.